The Role of Economic Education in Shaping Environmentally Sound Behavior (Case Study in Small and Medium Enterprises) - Yuliani, Y (Universitas Muhammadiyah Surakarta, 2018)
Education has a big role in shaping individuals who are ethical and moral and have a love and concern for the environment. Economic education also has a mandate to embody education for sustainable development through formal, informal and non-formal education channels. This study aims to obtain a holistic picture of the role of economic education in shaping environmentally sound behavior. The methodology used in this research is qualitative. The result of this research is that economic education obtained by SMEs does not always play a role in shaping environmental economic behavior. Therefore, economic education has a central role through the learning process carried out through the formal, informal and non-formal sectors.